2009
DOI: 10.1021/bi900564k
|View full text |Cite
|
Sign up to set email alerts
|

Human Replication Protein A−Rad52−Single-Stranded DNA Complex: Stoichiometry and Evidence for Strand Transfer Regulation by Phosphorylation

Abstract: The eukaryotic single-stranded DNA-binding protein, replication protein A (RPA), is essential in DNA metabolism and is phosphorylated in response to DNA-damaging agents. Rad52 and RPA participate in the repair of double-stranded DNA breaks (DSBs). It is known that human RPA and Rad52 form a complex, but the molecular mass, stoichiometry, and exact role of this complex in DSB repair are unclear. In this study, absolute molecular masses of individual proteins and complexes were measured in solution using analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…More recently, Shi and colleagues demonstrated by mutating the phosphorylation site of RPA that this posttranslational modification is required for Rad51 assembly (Shi et al, 2010). The importance of RPA phosphorylation during the presynaptic phase of HR was confirmed by Deng and colleagues who proposed a model in which RPA phosphorylation promotes Rad52 function and thus prepares DSB to be processed by Rad51 (Deng et al, 2009). Phosphorylation of the Rad52 mediator in a c-Abl dependant manner has also been described in response to ionizing treatment (Kitao and Yuan, 2002).…”
Section: Recruitment Of Rad51 At the Damage Site -Presynaptic Phase Omentioning
confidence: 96%
“…More recently, Shi and colleagues demonstrated by mutating the phosphorylation site of RPA that this posttranslational modification is required for Rad51 assembly (Shi et al, 2010). The importance of RPA phosphorylation during the presynaptic phase of HR was confirmed by Deng and colleagues who proposed a model in which RPA phosphorylation promotes Rad52 function and thus prepares DSB to be processed by Rad51 (Deng et al, 2009). Phosphorylation of the Rad52 mediator in a c-Abl dependant manner has also been described in response to ionizing treatment (Kitao and Yuan, 2002).…”
Section: Recruitment Of Rad51 At the Damage Site -Presynaptic Phase Omentioning
confidence: 96%
“…RAD52-RPA protein -protein interactions and posttranslational modifications may also play important roles in the annealing of complementary RPA-ssDNA complexes. For example, phosphorylated RPA, on interaction with RAD52, induces the handoff of ssDNA from RPA to RAD52 (Deng et al 2009). This suggests that there is a pathway for coupling the initiation of SSA or other annealing-dependent recombination processes to DNA damage signaling.…”
Section: Dna-annealing Proteins In Hrmentioning
confidence: 99%
“…If Rad52 is unable to release RPA from ssDNA and enable Rad51 exchange, the recombination would fail [74,75]. It has recently been reported that RPA phosphorylation can modulate HR repair [76][77][78], as the phosphorylation of RPA strengthens its interaction with Rad51 and Rad52 and is critical for Rad52-mediated Rad51 exchange and RPA dissociation from ssDNA [77]. This phenomenon is likely facilitated by the conformational change in phosphorylated RPA2.…”
Section: Homologous Recombination Repairmentioning
confidence: 99%